2014
DOI: 10.1371/journal.pone.0113423
|View full text |Cite
|
Sign up to set email alerts
|

gone early, a Novel Germline Factor, Ensures the Proper Size of the Stem Cell Precursor Pool in the Drosophila Ovary

Abstract: In order to sustain lifelong production of gametes, many animals have evolved a stem cell–based gametogenic program. In the Drosophila ovary, germline stem cells (GSCs) arise from a pool of primordial germ cells (PGCs) that remain undifferentiated even after gametogenesis has initiated. The decision of PGCs to differentiate or remain undifferentiated is regulated by somatic stromal cells: specifically, epidermal growth factor receptor (EGFR) signaling activated in the stromal cells determines the fraction of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Although we do not know how Tkv affects hh transcription, our genetic data suggest that Tkv acts upstream of Egfr, since overexpressing a constitutively active form of Egfr suppressed tkvKD -induced SCC accumulation. However, our RNA-seq results revealed that transcript levels of egfr and genes encoding Egfr ligand (Spitz) ( Tio et al., 1994 ) and modulators (Argos and Gone early) ( Klein et al., 2004 , Matsuoka et al., 2014 ) were not affected in somatic tkvKD ovaries. We speculate that non-canonical Dpp signaling may control Egfr at a post-transcriptional level, or it may influence the competence of ICs to respond to the Spitz signal.…”
Section: Discussionmentioning
confidence: 68%
“…Although we do not know how Tkv affects hh transcription, our genetic data suggest that Tkv acts upstream of Egfr, since overexpressing a constitutively active form of Egfr suppressed tkvKD -induced SCC accumulation. However, our RNA-seq results revealed that transcript levels of egfr and genes encoding Egfr ligand (Spitz) ( Tio et al., 1994 ) and modulators (Argos and Gone early) ( Klein et al., 2004 , Matsuoka et al., 2014 ) were not affected in somatic tkvKD ovaries. We speculate that non-canonical Dpp signaling may control Egfr at a post-transcriptional level, or it may influence the competence of ICs to respond to the Spitz signal.…”
Section: Discussionmentioning
confidence: 68%
“…7 F). However, the same pattern is seen for gone early ( goe) which can attenuate EGFR signaling [ 64 ], and a gene often induced by EGFR pathway activity, kekkon1 ( kek1 ) [ 65 ], does not decline from ECs to FSCs. Two fibroblast growth factor (FGF) ligands, pyramus ( pyr ) and thisbe ( ths ), decline from group 5 to group 1, while the FGF antagonist sprouty ( sty ) undergoes the converse change.…”
Section: Resultsmentioning
confidence: 92%
“…Gone early (Goe) is an inactive pseudopeptidase member of the M13 neprilysin family in Drosophila ( Matsuoka et al, 2014 ), with substitutions in all key active site positions ( Table 2 ). Goe is a type II transmembrane protein that was detected on germ cell membranes that interfaced with other germ cells, but not on neighboring somatic cells.…”
Section: Other Pseudometallopeptidasesmentioning
confidence: 99%